The Concept of Special Courts in the Settlement of Regional Head Election Cases in Indonesia - dodi jaya wardana; Sukardi .; Radian Salman (Universitas Muhammadiyah Surabaya, 2021)
A special court for the settlement of regional head election cases needs to be established / held for the settlement of cases for regional head elections and this special court is established before the implementation of regional head elections simultaneously nationally. This special court for regional head elections is nothing new, but something that already exists. Moreover, this special election court has been implemented in Uruguay. The authority of the Election Court in Uruguay appears to be very broad, covering everything related to elections, from the making of the regulations, the implementation, to the settlement of the case. The form and design of the special election court institutions must be adapted to the conditions of the temporary (ad hoc) Indonesian state under the Supreme Court and has the authority to handle all cases that arise in the election process, ranging from administrative cases and election crimes to dispute over results. Regional elections. Keywords: Special Courts, the Settlement, Regional Head.